Antidepressant use during pregnancy and the risk of gestational diabetes mellitus: a nested case–control study - Maëlle Dandjinou; Odile Sheehy; Anick Bérard (BMJ Open)
Objectives The aim of this study was to determine the association between antidepressant (AD) classes, types and duration of use during pregnancy and the risk of gestational diabetes mellitus (GDM).Design and setting A nested case–control study was conducted within the Quebec Pregnancy Cohort (QPC), a Canadian provincial database which includes data on all pregnancies and children in Quebec from January 1998 to December 2015.Primary outcome measures Gestational diabetes mellitus.Participants Cases of GDM were identified after week 20 of pregnancy and randomly matched 1:10 to controls on gestational age at index date (ie, calendar date of GDM) and year of pregnancy. AD exposure was assessed by filled prescriptions between the beginning of pregnancy (first day of last menstrual period) and index date. Conditional logistic regression models were used to estimate crude and adjusted odds ratios (aOR).Results Among 20 905 cases and 209 050 matched controls, 9741 (4.2%) women were exposed to ADs. When adjusting for potential confounders, AD use was associated with an increased risk of GDM (aOR 1.19, 95% CI 1.08 to 1.30); venlafaxine (aOR 1.27, 95% CI 1.09 to 1.49) and amitriptyline (aOR 1.52, 95% CI 1.25 to 1.84) were also associated with an increased risk of GDM. Moreover, the risk of GDM was increased with longer duration of AD use, specifically for serotonin norepinephrine reuptake inhibitors, tricyclic ADs and combined use of two AD classes. No statistically significant association was observed for selective serotonin reuptake inhibitors.Conclusion The findings suggest that ADs—and specifically venlafaxine and amitriptyline—were associated with an increased risk of GDM.